Growth Performance, Physiological Responses, and Histoarchitectural Changes in Juvenile Pangasianodon hypophthalmus under Different Environmental Salinities - Hany M. R. Abdel-Latif; Hamada A. Ahmed; Mustafa Shukry; Asmaa F. Khafaga; Bassem Khalil Elkhayat; Mohsen Abdel-Tawwab; Rehab A. Abd-elaziz (Fishes, 2023)
Environmental salinity is an important abiotic factor that directly affects the growth, metabolism, osmoregulatory processes, and physiological performance of fish. Herein, the effects of long-term salinity stress on juvenile Pangasianodon hypophthalmus have been evaluated. Fish were allotted in five triplicate groups and exposed to five different salinities (0.0, 4.0, 8.0, 12.0, and 16.0‰) for 56 days. After exposure, the final weight, weight gain percent, and specific growth rate were significantly decreased in groups reared in 8‰, 12‰, and 16‰ salinities. The feed intake was also significantly reduced in groups raised in water salinities of 12‰ and 16‰ compared with other groups. Conversely, the feed conversion ratio values were significantly increased in groups reared in water salinities between 8‰ and 16‰ compared with other groups. The lowest survival rates were observed in groups reared at salinities of 12‰ and 16‰ (91.1% and 77.8%, respectively). Body moisture (%) was significantly decreased, while crude protein and crude lipids (%) were significantly increased in groups exposed to salinities ranging from 8.0‰ to 16.0‰. Stress biomarkers (such as blood glucose, lactate, and cortisol levels) and oxidative stress indicators (such as carbonyl proteins, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX)) were significantly increased in groups exposed to different salinities compared with the control group, and their highest levels were in the group exposed to 16‰ salinity. The histoarchitectural changes were different among groups in relation to the salinity level. Moreover, the scored histopathological lesions showed a significant increase in groups exposed to different salinities compared with the control, and the highest scores were reported in groups exposed to the highest salinities (12‰ and 16‰). Based on the fitting curves, the present study suggests that P. hypophthalmus could tolerate salinities up to 8.0‰ with no mortalities; however, 4‰ salinity was more suitable with no adverse effects on the growth and little impact on histology and physiological responses.